CD147 blockade as a potential and novel treatment of graft rejection - Luan, Jing (Mol Med Rep, 2017)
Cluster of differentiation (CD)147 is highly involved in the T cell activation process. High CD147 expression is observed on the surfaces of activated T cells, particularly CD4+ T cells. In organ transplantation, it is important to prevent graft rejection resulting from the excessive activation of T cells, particularly CD4+ T cells, which exhibit a key role in amplifying the immune response. The present study aimed to investigate the effects of CD147 blockade in vitro and in vivo and used a transplant rejection system to assess the feasibility of utilizing CD147 antibody-based immunosuppressant drugs for the treatment of graft rejection. The effects of CD147 antibodies were evaluated on lymphocyte proliferation stimulated by phytohemagglutinin or CD3/CD28 magnetic beads and in a one-way mixed lymphocyte reaction (MLR) system in vitro. For the in vivo analysis, an allogeneic skin transplantation mouse model was used. CD147 antibodies were effective against lymphocytes, particularly CD4+T lymphocytes, and were additionally effective in the one-way MLR system. In the allogeneic skin transplantation mouse model, the survival of transplanted skin was extended in the CD147 antibody-treated group. Furthermore, the level of inflammatory cell infiltration in transplanted skin was reduced. CD147 blockade decreased the serum levels of interleukin (IL)-17 and the proportions of peripheral blood CD4+ and CD8+ memory T cells. The data demonstrated that CD147 blockade suppressed skin graft rejection, primarily by suppressing CD4+T and memory T cell proliferation, indicating that CD147 exhibits great potential as a target of immunosuppressant drugs.